Historic Urbanscapes for Tomorrow, Two Italian Cases: Genoa and Bologna - Bonfantini, G. Bertrando (European Spatial Research and Policy, 2015)
After a rather long silence, in the last fifteen years, heritage has progressively returned to urban agendas, and not just in Europe.The following pages reflect on the possible updated “structural” function of the historic parts of contemporary cities through the examples provided by two medium-sized Italian cities – Genoa and Bologna – characterized by the presence of an important urban heritage and specific urban policies and plans focused on renewing their possible role.